2006
DOI: 10.1603/0022-0493-99.3.1025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effectiveness of Coroplast Sticky Traps for Sampling Stable Flies (Diptera: Muscidae), Including a Comparison to Alsynite

Abstract: Stable flies, Stomoxys calcitrans (L.) (Diptera: Muscidae), are a blood-feeding pest of cattle worldwide. A new trapping material, Coroplast, was compared with Alsynite sticky traps based on the number, sex, and parity of stable flies caught. Coroplast sticky traps caught more stable flies than Alsynite (trap catches of 2384 versus 753 on 15 traps), with this increase attributed to catching more males (1531 versus 532) and nulliparous females (817 versus 175); parous catches were similar (36 versus 46). The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The lower transcript abundance of Stomoxys Rh6 relative to Drosophila could reflect a partial (but pronounced) replacement of ancestral Rh6 expression in R8 photoreceptors by the blue-sensitive Rh5 opsin or members of the Rh1 gene cluster. Of possible significance in this context, stable flies exhibit strong positive phototaxis in response to UV-and blue range light sources [22, 23, 111, 112]. Moreover, positive phototaxis to blue light increases in female flies after fertilization [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower transcript abundance of Stomoxys Rh6 relative to Drosophila could reflect a partial (but pronounced) replacement of ancestral Rh6 expression in R8 photoreceptors by the blue-sensitive Rh5 opsin or members of the Rh1 gene cluster. Of possible significance in this context, stable flies exhibit strong positive phototaxis in response to UV-and blue range light sources [22, 23, 111, 112]. Moreover, positive phototaxis to blue light increases in female flies after fertilization [24].…”
Section: Resultsmentioning
confidence: 99%
“…Since stable flies infrequently associate with their hosts, feeding only 1 to 2 times per day, on-animal and pesticide applications are less effective control efforts than those that integrate sanitation practices with fly population suppression by way of traps [21]. Given the importance of chemosensory and vision pathways, repellents have been identified that target stable fly chemosensory inputs and current trap technologies exploit stable fly visual attraction [22-24]. However, despite these efforts, consistent control of stable fly populations remains challenging and development of novel control mechanisms is greatly needed.…”
Section: Introductionmentioning
confidence: 99%
“…On the Yellow Sticky Strips, pressure-sensitive adhesive captured fewer non-target insects than polybutene, possibly because the adhesive entangled the insects more than the thinner, less viscous pressure-sensitive adhesive. This could be a reason why polybutene adhesive caught more stable flies, Stomoyxs calcitrans (L.), than pre-coated plastic sheets (Beresford and Sutcliffe 2006). The Yellow Sticky Strips caught almost no beneficial bees and wasps, whereas the folded Alpha Scents board with pressure-sensitive adhesive captured high numbers of these insects.…”
Section: Discussionmentioning
confidence: 99%
“…The response to specific wavelengths can be manipulated in the design of traps, and the incorporation of ultraviolet reflective fiberglass panels (e.g. Alsynite ® ; Alsynite One NZ Ltd, Hamilton, New Zealand) has proved particularly effective (Beresford & Sutcliffe, 2006). Traps made from Alsynite, a translucent fiberglass, were originally developed by Williams (1973) and have subsequently become widely used (Gersabeck & Merritt, 1983;Broce et al, 1991).…”
Section: Introductionmentioning
confidence: 99%